Experimental study on perfobond strip connector in steel–concrete joints of hybrid bridges. (March 2016) - He, Shaohua; Fang, Zhi; Fang, Yawei; Liu, Ming; Liu, Liyang; Mosallam, Ayman S.
Abstract: Perfobond strip (PBL) connectors, consisting of a perforated steel plate with steel rebar passing through the holes and embedded in concrete to transfer the shear action between the concrete and steel components, are increasingly used in composite and hybrid girders and columns. Though many studies on the behavior of PBL connectors can be found in the literature, the load transferring mechanism of PBL still needs further clarification because noticeable discrepancies can be found among the existing equations for predicting the shear capacity of the connectors. This paper presents an experimental study of the structural response of PBL connectors under push-out loading. Twelve push-out specimens fabricated according to the design used for the connectors in the steel–concrete joints in a hybrid cable-stayed bridge have been investigated. The behavior of the connectors, including the failure modes, ductility, and the components of the ultimate shear-resistant capacity, is discussed in depth. The results indicate that the mechanical properties of the PBL specimens are improved due to the bond at the interface between the perforated plate and the concrete. The transverse rebar located in the center of the steel plate hole is important for ensuring the connector's ductility. Furthermore, an analytical model and corresponding equation for predicting the ultimate resistance of PBL connectors with shear failure of the dowel are proposed, and the feasibility of the developed equation has been verified by the experimental results from related references. Highlights: The behavior of PBL connector in steel–concrete joint is studied by push-out tests. The interfacial bonding effects between perforated plate and concrete are investigated. Constitutive analysis of the shear-resistant capacity in PBL connectors is performed. Equations are proposed to predict the shear capacity of PBL in steel–concrete joint.